Signage, Adi Marzban Path - Ghosh, Ayan (2023)
Named after Adi Pherozeshah Marzban (1914–87), Adi Marzban Path is where the office of Jam-e-Jamshed (Marzban was its editor) originally stood. Asia’s second oldest running newspaper, Jam-e-Jamshed was launched in 1832, by Adi's great-grandfather, Fardoonjee Marzban. A doyen of Parsi theatre, Adi Marzban was awarded the Padma Shri in 1964.